2009
DOI: 10.1126/science.1162818
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Nuclear Translocator Alters CD30-Mediated NF-κB–Dependent Transcription

Abstract: Expression and signaling of CD30, a tumor necrosis factor (TNF) receptor family member, is upregulated in numerous lymphoid-derived neoplasias, most notably anaplastic large cell lymphoma (ALCL) and Hodgkin's lymphoma (HL). To gain insight into the mechanism of CD30 signaling, we used an affinity purification strategy that led to the identification of the aryl hydrocarbon receptor nuclear translocator (ARNT) as a CD30 interacting protein that modulated the activity of the RelB subunit of the transcription fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 27 publications
3
66
0
Order By: Relevance
“…11), in support of the latter model. Although no report has shown that GATA3 functions in a manner other than as a classical DNA binding transcription factor (as does, for example, Scl/Tal1 [65] or the aryl hydrocarbon nuclear translocator [66]), such a binary function for GATA3 cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…11), in support of the latter model. Although no report has shown that GATA3 functions in a manner other than as a classical DNA binding transcription factor (as does, for example, Scl/Tal1 [65] or the aryl hydrocarbon nuclear translocator [66]), such a binary function for GATA3 cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an intra-cytoplasmic interaction of HIF1 with CD30 has been identified in ALK þ TCL cells resulting in the modulation of nuclear factor-kB activity (Wright and Duckett, 2009). However, only HIF1a, or the aryl hydrocarbon nuclear translocator, was involved in the complex.…”
Section: Npm/alk-stat3 Pathway Induces Hif1a Expression M Marzec Et Almentioning
confidence: 99%
“…Moreover, ARNT might also promote survival and proliferation of tumor cells, independently of its roles in AhR and HIF signaling. For example, it has been reported that ARNT increases binding of RelB to DNA (reflecting activation of the non‐canonical NF‐κB pathway) to block the activity of RelA‐p50 dimers, indicating inhibition of the canonical NF‐κB pathway 17. Furthermore, unlike normal lymphocytes that express equal levels of 2 ARNT isoforms (isoforms 1 and 3), malignant lymphoid cell lines (eg, human MM and anaplastic large cell lymphoma cells) exhibit higher levels of isoform 1, which might potentiate cell proliferation by antagonizing RelB and p53‐dependent cell cycle arrest and apoptosis 18.…”
Section: Introductionmentioning
confidence: 99%